(untitled) (Diversity Research: Journal of Analysis and Trends, 2023)
In this article, there is a system of directing students to the profession diagnosing career orientation based on problems, interests and inclinations, his tasks, main directions and mechanisms of its implementation are mentioned. Experience of career orientation by diagnosis of educational activity methods are shown, factors influencing career guidance and ways to eliminate them are provided, as well as suggestions and recommendations system is presented.